Biophysical investigations of molecular mechanisms of chemotherapeutic agents action. 1. Chemotherapeutic and antiviral agents (Review) - Kosevich, M. V.; Ryazanova, O. A.; Pashynska, V. A. (Biophysical Bulletin, 2019)
Background: Determination of molecular mechanisms of action of drugs forms a scientific basis for the directed search of efficient medications. Assumed pathways of interactions of chemotherapeutic drugs which affect infectious agents and malignant neoplasm with their potential molecular targets require direct evidences at the molecular level. Such evidences can be obtained by means of molecular biophysics which possesses an arsenal of new powerful physical techniques for studying the intermolecular interactions of biomolecules and pharmaceutical agents. Objectives: The aim of this review is the generalization of the results of long standing investigations on the molecular mechanisms of action of chemotherapeutic agents performed in the biophysical departments of B. Verkin Institute for Low Temperature Physics and Engineering (ILTPE) of the NAS of Ukraine. The first part of the review is devoted to anticancer and antiviral agents targeted presumably at nucleic acids. Materials and methods: Mass spectrometric studies of molecules of thermally unstable drugs and their complexes with biomolecules have been advanced significantly due to the development of soft ionization/desorption techniques; the researchers of ILTPE have made noticeable contribution to this field. The methods of molecular spectroscopy and computer modeling by means of quantum chemistry were applied in the combined investigations. Results: The objects of study were the systems composed of chemotherapeutic drugs – thiophosphamide, phenazine derivatives and phenazine-modified antigene/antisense oligonucleotides, quaternary compounds, tilorone – and their molecular targets – DNA, oligo- and polynucleotides and nucleic acids components. The mechanisms of action of these drugs established at the model molecular level consisted in the specific and nonspecific noncovalent or covalent interactions of the drugs’ molecules with nucleic acids and their components and in the formation of stable drug-target complexes. Conclusions: The experience of investigations conducted during several decades at the ILTPE has demonstrated the efficiency of the application of the methods and approaches of molecular biophysics to establishing of molecular mechanisms of drugs action. The basic results obtained are of practical importance for the further development of new efficient pharmaceuticals.